Intrachromosomal Looping and Histone K27 Methylation Coordinately Regulates the lncRNA H19-Fetal Mitogen IGF2 Imprinting Cluster in the Decidual Microenvironment of Early Pregnancy - Xue Wen; Qi Zhang; Lei Zhou; Zhaozhi Li; Xue Wei; Wang Yang; Jiaomei Zhang; Hui Li; Zijun Xu; Xueling Cui; Songling Zhang; Yufeng Wang; et al. (Cells, 2022)
Recurrent spontaneous abortion (RSA) is a highly heterogeneous complication of pregnancy with the underlying mechanisms remaining uncharacterized. Dysregulated decidualization is a critical contributor to the phenotypic alterations related to pregnancy complications. To understand the molecular factors underlying RSA, we explored the role of longnoncoding RNAs (lncRNAs) in the decidual microenvironment where the crosstalk at the fetal–maternal interface occurs. By exploring RNA-seq data from RSA patients, we identified H19, a noncoding RNA that exhibits maternal monoallelic expression, as one of the most upregulated lncRNAs associated with RSA. The paternally expressed fetal mitogen IGF2, which is reciprocally coregulated with H19 within the same imprinting cluster, was also upregulated. Notably, both genes underwent loss of imprinting, as H19 and IGF2 were actively transcribed from both parental alleles in some decidual tissues. This loss of imprinting in decidual tissues was associated with the loss of the H3K27m3 repressive histone marker in the IGF2 promoter, CpG hypomethylation at the central CTCF binding site in the imprinting control center (ICR), and the loss of CTCF-mediated intrachromosomal looping. These data suggest that dysregulation of the H19/IGF2 imprinting pathway may be an important epigenetic factor in the decidual microenvironment related to poor decidualization.